2005
DOI: 10.1097/01.ta.0000196434.88182.77
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital Endotracheal Intubation and Positive Pressure Ventilation Is Associated with Hypotension and Decreased Survival in Hypovolemic Trauma Patients: An Analysis of the National Trauma Data Bank

Abstract: Pre-hospital endotracheal intubation in trauma patients is associated with hypotension and decreased survival. This may be mediated by the effect of positive pressure ventilation during hypovolemic states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…In the prehospital setting, several studies have explored the efficacy of ETI in trauma and pediatric patients. [38][39][40][41][42] These studies have suggested that prehospital ETI may lead to an increase in mortality in these specific patient populations, although their retrospective, nonrandomized designs do not permit evaluation of casuality. Results from the current study indicated that individuals experiencing OOHCA may be another subset of prehospital patients who experience increased mortality when receiving prehospital ETI.…”
Section: Discussionmentioning
confidence: 99%
“…In the prehospital setting, several studies have explored the efficacy of ETI in trauma and pediatric patients. [38][39][40][41][42] These studies have suggested that prehospital ETI may lead to an increase in mortality in these specific patient populations, although their retrospective, nonrandomized designs do not permit evaluation of casuality. Results from the current study indicated that individuals experiencing OOHCA may be another subset of prehospital patients who experience increased mortality when receiving prehospital ETI.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Current thinking prioritizes methods for the decrease of pre-hospital time by addressing only life-threatening injuries through control of bleeding, cervical-spine stabilization, and similar interventions. [23] Rapid transport to the hospital is critically important. [24] In the current study, the interval between the accident and hospitalization was 41.3±79.8 minutes and most patients arrived at the hospital 30-60 minutes after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Key objective data points collected were defined as factors known to affect patient care or outcomes during EMS and ED care transfers (2,3,(6)(7)(8)(9)(10)(11)(12). The tabulated information included heart rate, blood pressure, respiratory rate, the Glasgow Coma Scale/level of consciousness (GCS/LOC), and eight demographic data points (i.e., age, medical history, allergies, medications, events surrounding the chief complaint, active problems/ injuries, intravenous access, and treatment given before arrival).…”
Section: Data Collectionmentioning
confidence: 99%